AN ETHNOGRAPHY ON THE WEDGE SEA HARE IN MACTAN ISLAND, THE PHILIPPINES - Takashi Tsuji (Naditira Widya, 2019)
The wedge sea hare (Dolabella auricularia) is a mollusk species found in tidal flats and is consumed as food around the Philippines. The practice of consuming its internal organs is probably found only on the Mactan Island. The Problem of this study is to clarify why people collect the internal organs of wedge sea hare. The objective is a gleaner who have special skills to identify the sea hare burrows. Participatory observation and measurement method were employed for this research. As a result, it found that the gleaners precisely identify occupied sea hare burrows using unique skills, and to remove the edible internal organs from the disposable body. Local people regard the internal organs as a nutrition. As a conclusion, this practice must be an adaptation to an environment where vegetable protein is scarce due to a limestone-based soil unsuitable for agriculture. Thus, the role of the wedge sea hare in a unique culture was also developed. Kelinci laut (Dolabella auricularia) adalah spesies moluska yang ditemukan di dataran pasang surut dan dikonsumsi sebagai makanan di sekitar Filipina. Praktik mengkonsumsi organ internalnya mungkin hanya ditemukan di Pulau Mactan. Masalah penelitian ini adalah untuk menjelaskan mengapa orang mengumpulkan organ internal kelinci laut. Tujuannya adalah seorang pengumpul yang memiliki keterampilan khusus untuk mengidentifikasi lubang kelinci laut. Metode pengamatan dan pengukuran partisipatif digunakan untuk penelitian ini. Sebagai hasilnya, ditemukan bahwa para pengumpul secara tepat mengidentifikasi lubang yang didiami kelinci laut dengan menggunakan keterampilan unik, dan mengeluarkan organ internal yang dapat dimakan dari tubuh yang bisa dibuang. Masyarakat lokal menganggap organ dalam sebagai nutrisi. Sebagai kesimpulan, praktik ini harus merupakan adaptasi terhadap lingkungan di mana protein nabati langka karena tanah berbahan dasar batugamping yang tidak cocok untuk pertanian. Dengan demikian, peran kelinci laut dalam budaya unik juga dikembangkan.